Structural Brain Correlates of Attention Dysfunction in Lewy Body Dementias and Alzheimer’s Disease - Cromarty, Ruth A.; Schumacher, Julia; Graziadio, Sara; Gallagher, Peter; Killen, Alison; Firbank, Michael J.; Blamire, Andrew; Kaiser, Marcus; Thomas, Alan J.; O’Brien, John T.; Peraza, Luis R.; Taylor, John-Paul (Frontiers in Aging Neuroscience, 2018)
Lewy body dementia (LBD) and Alzheimer’s disease (AD) are common forms of dementia that have different clinical profiles but are both commonly associated with attentional deficits. The aim of this study was to investigate efficiency of different attentional systems in LBD and AD and its association with brain structural abnormalities. We studied reaction time (RT) data from 45 LBD, 31 AD patients, and 22 healthy controls using the Attention Network Test to assess the efficiency of three different attentional system: alerting, orienting, and executive conflict. Voxel-based morphometry was used to investigate relations between different attention components and cortical volume. Both dementia groups showed slower overall RTs than controls, with additional slowing in LBD relative to AD. There was a significant alerting effect in controls which was absent in the dementia groups, the executive conflict effect was greater in both dementia groups compared to controls, but the orienting effect did not differ between groups. Mean RT in AD was negatively correlated with occipital grey matter volume and in LBD orienting efficiency was negatively related to occipital white matter volume. Given that previous studies in less impaired patients suggest a maintenance of the alerting effect, the absent alerting effect in our study suggests a loss of alerting efficiency with dementia progression. While orienting was largely preserved, it might be related to occipital structural abnormalities in LBD. Executive function was markedly impaired in both dementia groups, however, the absence of relations to brain volume suggests that it might be more related to functional rather than macrostructural pathophysiological changes.